TRANSFORMATION OF STRUCTURE OF MYTHOLOGICAL REPRESENTATIONS OF MOUNTAINEERS DURING A MODERNIST STYLE ERA - Svitlana Lytvyn-Kindratiuk (Vasyl Stefanyk Precarpathian National University, 2015)
In article approach to studying of structure of mythological representations of mountaineers during an era of modernization and globalization of a way of life is considered. The Psikhologo-historical foreshortening of the analysis allows to track communication of features of environment and difficulties of coordination to structure of primary and latest mythological representations of Huzuls.